The Effect Of Market Orientation To Firms Performance With The Management Accounting System As A Mediating - Margareta Alda Amanda Devi; Khairina Nur Izzaty (Accounting and Finance Studies, 2021)
Market orientation is a strategy consisting of three components, namely customer orientation, participant orientation, and coordination between functions. The management accounting system is a system that can produce information, both in the form of financial information and non-financial information. The purpose of this study was to analyze the effect of market orientation on company performance variables with the mediation management accounting system. This research was conducted at MSMEs in the fisheries sub-sector at TPI Tasikagung II, Rembang Regency. The samples taken were 56 people. The data obtained were then processed using the SmartPLS3 test tool. The results showed that market orientation had an effect on company performance. Market orientation and management accounting systems can influence decision making. The management accounting system has an effect on company performance. Market orientation affects company performance through the management accounting system.